The Impact of Employee Engagement on Task Performance - DR. HAZRAT BILAL; ARSHAD ALI KHAN; KHURSHEED AHMAD; DR.SYED NASEEB ULLAH SHAH (Journal of Business & Tourism, 2021)
In developed countries of the world, many studies have been carried out on the link between engagement and task performance in different context. Ignorable studies are conducted in developing countries like Pakistan. The aim of the present study was to explore potential link between engagement and task performance. This link was analyzed through statistical techniques called Pearson Correlations and Regression. The data was gathered through self-administered questionnaire distributed among teaching faculty working in the private owned universities. A total of 224 questionnaire were returned by respondents. After analyzing these questionnaires the results showed that there was positive connection in engagement and task performance and thus confirmed the hypothesis of the study.